The Perception of Students Regarding the Importance of Professionalism of Guidance and Counseling Teachers in School (Literasi Nusantara, 2023)
In schools, guidance and counseling play an important role in relation to student development, in terms of services that generally relate directly to students. Of course, the tutor must be close and have a good image of the student in order to maintain trust and intimacy with the tutor. To collect and analyze a variety of articles, journals, books, and other reading materials relevant to students' perceptions of This study draws on a literature survey. Research has shown that students rate the professionalism of their tutors in schools as good, but this does not mean that tutors are perceived negatively, they do not have a defined job. , citing Raid Teachers, Picket Teachers, and others. It is already completely gone, and each leader and tutor needs to be empowered and insightful